An Investment Framework for Nutrition in Kenya - Eberwein, Julia Dayton (Washington, DC: World Bank, 2017)
This knowledge brief presents the costs of scaling up key effective nutrition interventions in Kenya and compares different scale-up scenarios to determine which one produces the best results for the lowest cost. The goal of the analysis is to inform program planning by identifying the most cost-effective packages of interventions and by leveraging additional resources from domestic budgets and development partners.